ANALISIS YURIDIS TERKAIT PERSYARATAN BEBAS BERSYARAT ABU BAKAR BA’ASYIR - Mardiana Andresa P; Erdianto Erdianto; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The state guarantees the rights of prisoners as regulated in Article 14 paragraph (1) of the Law of the Republic of Indonesia Number 12 of 1995 concerning Corrections. One of the rights guaranteed in the correctional law is parole. The government plans to release Abu Bakar Ba'asyir for humanitarian reasons, so it immediately reaps the many pros and cons. Apart from the political factors that arose with the plan to release Abu Bakar Ba'asyir, it is important to study it from legal analysisThis type of research can be classified as normative legal research, namely legal research carried out by examining library materials. In this study, the authors conducted research on legal principles using descriptive methods. The data collection technique used in Normative Law Research is a library research method, namely using the library as a means of collecting data, by studying books as reference material related to the problems to be studied.The conclusion that can be obtained from the research results is that the process of granting parole to terrorism convict Abu Bakar Ba'asyir who invites controversy in a juridical perspective, there are general conditions and special conditions. Granting parole for terrorism convicts is different from granting parole for general prisoners. Terrorism convicts must attach a certificate of having participated in the Deradicalization Program from the Head of Prisons and / or the Head of the National Counterterrorism Agency. As for the object that becomes the Controversy Polemic of Abu Bakr Ba'asyir's parole, there is a requirement for Abu Bakar Ba'asyir, there are conditions that must be met. Efforts that have been made to resolve the Abu Bakar Ba'asyir Controversy in Criminal Law Perspective by referring to the continued legal basis related to parole which regulates the conditions for conditional release for terrorism convicts to be fulfilledKeywords: Legal Analysis, Controversy, Parole, Abu Bakar Ba'asyir